Regional political ecologies and environmental conflicts in India - Pattanaik, Sarmistha; Sen, Amrita (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book focuses on the regional political ecologies (RPEs) of environmental conflicts in India. It explores broadly, landscape-based analyses of political, economic and social issues, which impact environmental changes, challenges and conflicts at local and micro-local levels. The chapters in this volume examine the intervention of different stakeholders in the management of various regional ecological landscapes in India, including forests, rivers, canals, creeks and wetlands. The volume is an interdisciplinary endeavour, weaving together contextual narratives through a combination of approaches from sociology, anthropology, geography, political studies and environmental history. Using such core approaches, the book studies the place-based dynamisms within the regional environmental conflicts in the selected conservation landscapes. It provides empirical reflections on transboundary issues, rural-urban transitions, middle-class environmentalism, identity conflicts, decentralized natural resource management and the role of political institutions. Regional Political Ecologies and Environmental Conflicts in India will be of great interest to students and scholars of Political Ecology and South Asian Environmental Studies"--
Introduction: Understanding Regional Political Framings of Environmental Conflicts in India -- Heritage or Basic Human Rights? Politics of Environmentalism Surrounding the Adi Ganga in Kolkata -- The Opportunities and Challenges of Transboundary Conservation: Solutions in Adaptive Management -- Riverbank Erosion and Inter-Community Relationships in Majuli: Political Implications of a Changing Landscape in Assam -- A Regional Political Ecology of the Changing Cityscape and the Crisis of Conservation of the East Kolkata Wetlands (EKW), India -- Land Ownership and Ecological Knowledge Production from a Gender and Power Dynamics Perspective in a Village in Nagaland -- Political Ecology of Natural Resource Governance in Chhattisgarh, India: Critical Ethnographic Reflections on the Vulnerable Livelihoods of the Scheduled Tribes in Bastar.
Keywords: Political ecology -- India -- Case studies; Environmental policy -- India -- Case studies; Conflict management -- India -- Case studies; Landscape ecology -- India -- Case studies; Interdisciplinary approach in education; NATURE / Ecology; NATURE / Environmental Conservation & Protection; POLITICAL SCIENCE / Public Policy / Environmental Policy